Gender Bias in Cross-Allegation Domestic Violence-Parental Alienation Custody Cases: Can States Legislate the Fix? - Jaffe-Geffner, Nina (Columbia Journal of Gender and Law, 2022)
“Parental Alienation Syndrome” (PAS), developed by Dr. Richard Gardner in 1985, posits that a frequent dynamic in child custody disputes involves vengeful mothers falsely convincing their children that they have been sexually abused by their fathers. Although PAS is widely discredited and courts have ruled it inadmissible, new formulations of the theory, such as Parental Alienation (PA), continue to play a dominant role in custody proceedings. Proponents of PA assign the label to a broad range of custody cases in which children favor one parent and reject the other. However, despite the seemingly more gender-neutral framing of PA, empirical research shows that courts use PA to discredit mothers’ allegations of domestic violence and abuse and justify custody switches away from the mother. This Note analyzes the gender bias in family courts’ handling of custody cases involving cross-allegations of domestic violence and PA, and then proposes four legislative provisions aimed at reducing the effects of such bias in custody proceedings.